Anticipatory salivary cortisol and state anxiety before competition predict match outcome in division I collegiate wrestlers - Cintineo, P. H.; Arent, M. S. (The Journal of Strength and Conditioning Research, 2019)
Anticipation of exercise and other stressors has been shown to result in physiological and psychological changes, which include increased levels of cortisol and anxiety. Combat sports, in particular, typically elicit robust anticipatory responses because of the distinct nature of these sports. Therefore, the purpose of this investigation was to examine the relationship between state anxiety scores, anticipatory cortisol response, and performance outcomes in college wrestlers. A secondary purpose was to determine the correlation between anticipatory cortisol and state anxiety scores. Twenty-six collegiate wrestlers were recruited to undergo saliva collection and to complete the State Anxiety Inventory before a wrestling match and again on a rest day in a time-matched, control session. Univariate analyses revealed that both salivary cortisol and anxiety were greater before competition than on a rest day. In addition, it was found that losers had higher levels of anticipatory cortisol and anxiety compared with winners. A significant correlation between salivary cortisol and anxiety was found as well. These data show that higher cortisol and anxiety may negatively affect performance. Athletes and coaches should work together to determine optimal levels of arousal and should aim to replicate this during both training and competition to ensure consistently high levels of performance through appropriate preparation.